2007
DOI: 10.1345/aph.1h365
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate Use for Cushing's Syndrome Caused by an Ectopic Adrenocorticotropic Hormone–Producing Tumor

Abstract: When oral or enteral medications cannot be administered and sedation is required in critically ill patients, etomidate is an appropriate intravenous agent for hypercortisolemia. There were no obvious problems with stability when undiluted etomidate 2 mg/mL was infused through a dedicated central venous catheter lumen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Studies have demonstrated that etomidate directly inhibits adrenal steroidogenesis [32,33] and the primary mode of action is thought to be inhibition of 11β-hydroxylation of gluco- and mineralocorticoids [6,34,35]. These studies, in patients and adrenal cell lines, consistently show a rise in 11-deoxycortisol and 11-deoxycorticosterone associated with a decrease in cortisol and corticosterone concentrations after low-dose etomidate administration [6,16,34,35,36,37,38,39,40]. However, higher concentrations of etomidate result in a reduction in 17α-OH-progesterone and progesterone concentrations, suggesting inhibition of other cytochrome P450-dependent enzymes, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that etomidate directly inhibits adrenal steroidogenesis [32,33] and the primary mode of action is thought to be inhibition of 11β-hydroxylation of gluco- and mineralocorticoids [6,34,35]. These studies, in patients and adrenal cell lines, consistently show a rise in 11-deoxycortisol and 11-deoxycorticosterone associated with a decrease in cortisol and corticosterone concentrations after low-dose etomidate administration [6,16,34,35,36,37,38,39,40]. However, higher concentrations of etomidate result in a reduction in 17α-OH-progesterone and progesterone concentrations, suggesting inhibition of other cytochrome P450-dependent enzymes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…side-chain cleavage enzyme, P450scc or possibly 17α-hydroxylase [41,42,43,44,45,46,47]. The use of etomidate to suppress hypercortisolaemia in adult patients has previously been reported [16,36,37,48,49,50]. In the majority of case reports, the severe hypercortisolaemia was secondary to ectopic ACTH syndrome [16,36,37,38], although etomidate has also been used in CD and adrenal adenomas [39].…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity due to propylene glycol may occur in high doses and the WHO suggests that the maximum oral safe intake is 25 mg/kg daily (101). Although propylene glycol is administered intravenously in the case of etomidate administration, propylene toxicity is unlikely to occur in the low doses needed for cortisol suppression and it appears to be safe even at higher doses in situations where sedation for ventilation was desired as well (0.06-0.03 mg/kg per h) (102). Prolonged administration (5.5 months) of the propylene glycol preparation of etomidate was reported in a 39-year-old patient with the EAS who was unable to have oral medications; in order to reduce the total dose needed, etomidate was given as a dose-titration regimen and the dose was adjusted during an episode of acute renal failure with no significant adverse effects (96).…”
Section: Etomidatementioning
confidence: 99%
“…Etomidate is the only parenteral active steroidogenesis inhibitor and should be used in cases where rapid control of hypercortisolaemia is vital and an oral agent is contraindicated (9,102,116,117,118). In addition, it can be very useful in situations where sedation is a desired effect, such as patients requiring intubation for respiratory support or patients with acute psychosis.…”
Section: Choice Of Agentmentioning
confidence: 99%
“…Intravenous etomidate therapy may be considered in situations where rapid control of cortisol levels is required and oral therapy is not advisable (34). It can be a bridge to definitive treatment, such as surgery for primary tumor, bilateral adrenalectomy, or until the action of a slow-onset adrenolytic agent or steroidogenesis inhibitor starts.…”
Section: Treatment and Managementmentioning
confidence: 99%